2019
DOI: 10.1021/acssuschemeng.9b05124
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics Analysis for an Upflow Integrated Anaerobic Digestion Reactor with Microbial Electrolysis under Different Hydraulic Retention Times: Effect of Bioelectrode Spatial Distribution on Functional Communities Involved in Methane Production and Organic Removal

Abstract: The electrode plays a significant role in an integrated anaerobic digestion reactor with microbial electrolysis that can increase energy production. Optimizing electrode positions by means of hydrodynamic analysis was proven feasible. In this work, different spatial distributions of bioelectrodes in upflow integrated anaerobic digestion reactors were researched to obtain a highly effective configuration. The hydrodynamic characters of each reactor were evaluated by a residence time distribution (RTD) test and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The hydrodynamic behavior of the reactor can also be tested by computational fluid dynamics and residence time distribution simulation. Geo et al reported that, if the electrode is kept at the bottom of the reactor with the anode placed below the cathode, the maximum methane generation of 304.5 mL occurs in CH 4 L –1 of reactor day –1 , with a maximum COD removal of 92.1%. Kim et al fabricated 12 MFCs with different internal structures.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrodynamic behavior of the reactor can also be tested by computational fluid dynamics and residence time distribution simulation. Geo et al reported that, if the electrode is kept at the bottom of the reactor with the anode placed below the cathode, the maximum methane generation of 304.5 mL occurs in CH 4 L –1 of reactor day –1 , with a maximum COD removal of 92.1%. Kim et al fabricated 12 MFCs with different internal structures.…”
Section: Resultsmentioning
confidence: 99%
“…The use of horizontally oriented electrodes in upflow anaerobic bioreactors with built-in electrochemical system had also been investigated. It has been found that the optimal design in such a case occurred when the working electrode was placed at the bottom (Gao et al 2020 ). However, most of current researchers only focused on lab-scale reactors (e.g., volume less than 500 mL) (Jiang et al 2019 ) and only wastewater, glucose or food waste have been utilized as substrates to perform electrochemical fermentation (Jiang et al 2020 ; Liu et al 2019b ; Zhou et al 2019 ).…”
Section: Proposed Strategies For Vfa Productionmentioning
confidence: 99%
“…To overcome the harmful effects of low interaction e ciency between bacteria and anode material, studies have shown that high shear rates (below the tensile strength level) lead to stronger microbial aggregation and more compact bacterial colony structures (Jones &Buie 2019, Pham et al 2008, Pinck et al 2020. High shear can be realized by prolonging hydraulic retention times (Gao et al 2019), rotating anode electrodes (Pan et al 2019) and applying agitation to the cathode chamber (Islam et al 2019). For instance, it has been reported that the power and current densities of polydimethylsiloxane (PDMS)-based microscale MFCs increase with increasing ow rate and that maximum power densities and current densities were 0.71 mW/m 2 and 1.8 mA/m 2 , respectively, which higher than that were realized by previous PDMS-based micro MFCs (Yoon et al 2018).…”
Section: Introductionmentioning
confidence: 99%